Gambaran Risiko Ergonomi dan Keluhan Muskuloskeletal pada Perawat di Rsud Datu Beru Takengon - Khairuman Khairuman; Izzatul Munira; Maizzatul raziah; Bayani Bayani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Ergonomic risk is one of the factors contributing to musculoskeletal disorders in nurses due to work activities such as lifting patients, maintaining non-ergonomic postures, and performing repetitive movements. These conditions can impact the health of healthcare workers, work productivity, and the quality of nursing services. This study aims to describe the level of ergonomic risk and musculoskeletal complaints in nurses at Datu Beru Takengon Regional General Hospital. The study used a quantitative descriptive design with a cross-sectional approach. The subjects were nurses working in several hospital service units. Ergonomic risk assessment was carried out using the Rapid Entire Body Assessment (REBA), while musculoskeletal complaints were measured using the Nordic Body Map (NBM). Analysis was carried out univariately and presented in the form of frequency distribution and percentage. The evaluation results showed that there was still exposure to ergonomic risks in nurses' work activities. Musculoskeletal complaints were predominantly found in the neck, shoulders, back, and waist areas. Factors suspected of contributing include manual patient transfer activities, non-ergonomic work postures, and limited utilization of ergonomic support facilities. Ergonomic risks are still found among nurses at Datu Beru Takengon Regional Hospital and have the potential to increase the incidence of musculoskeletal disorders. Strengthening the ergonomics program through training, providing supporting facilities, and regular evaluations is needed.